PENDAMPINGAN PEMBUATANMEDIAVELTIKULTURUNTUKPENANAMAN TUMBUHAN OBATDALAM PEMAKSIMALAN PEKARANGAN RUMAH - Moh. Hasyim (UII, 2013)
Yard of the house is an area that is close to home building. Yard of a house canhave benefits if properly managed. Vertikultur a suitable planting cultivation techniquesapplied in the yard. Vertikultur is a way of farming vertically toward the free space.Vertikultur ie saving advantages over land, water, and fertilizer. The resulting plants arealso more fertile, have more branches, and quickly harvested. Vertikultur plantingmedium can use PVC pipe, bamboo, polybag, or pot. Vertikultur on drugs that are notwoody plants can be hung on the gutters. Medicinal plants can be propagated using ropespread. The medicinal plant itself serves as first aid on the family when sick. The purposeof this paper is to examine the utilization of productive land yard of the house as a familyfor cultivation of medicinal plants with vertikultur techniques.